Diversity of Heterocapsa (Dinophyceae) and the algal bloom event in the mariculture areas of Johor Strait, Malaysia - Roziawati, Mohd Razali; Nurin Izzati, Mustapa; Ku Kassim, Ku Yaacob; Fadzilah, Yusof; Sing Tung, Teng; Afiqah Hamilton, Hanifah; Soon Hii, Kieng; Monaliza, Mohd Din.; Haifeng, Gu; Pin Leaw, Chui; Teen Lim, Po (J-Stage, 2022)
In November 2020, a high biomass multi-species algal bloom caused heavy water discoloration in the fish and mussel farm areas of the Johor Strait, Malaysia. A total of 19 microalgal taxa were identified from the plankton samples collected during the bloom event. Eleven genera were diatoms, and eight genera were dinophytes. The microalgal composition was dominated by the diatom Guinardia sp., with an average cell density of 1.7×106 cells L−1 , making up 65–80% of the phytoplankton composition. Concomitantly, high densities of the dinophytes Heterocapsa minima (3.8–5.3×105 cells L−1 ) and Karlodinium spp. (3.5–6.6×103 cells L−1 ) were found. This is the first record of the occurrence of H. minima in Malaysian waters. Detailed morphological observations of H. minima based on scanning electron microscopy are presented in this study. To have a better insight into the Heterocapsa species assemblages in the Johor Strait, the diversity of Heterocapsa species assemblages along the strait was investigated based on a metabarcoding approach. Environmental DNA collected between 2018 and 2019 was used for high throughput amplicon sequencing targeting the small subunit (SSU) ribosomal RNA gene marker. The metabarcoding analysis detected three rare Heterocapsa species in the waters, H. niei, H. rotundata, and H. steinii. The results showed that Heterocapsa species assemblages varied temporally across the strait, with higher species diversity and amplicon sequence variant (ASV) read abundances detected in the Eastern Johor Strait. Although no fish/shellfish kills were sighted during the 2020 bloom event, the presence of harmful microalgal species, such as Heterocapsa minima and Karlodinium spp., urged the need for a comprehensive HAB monitoring program in the Strait to safeguard the aquaculture industry in the areas.